DISSECTING AORTIC ANEURYSM IN REAL–LIFE CLINICAL PRACTICE: DIAGNOSTICS, TREATMENT AND PROGNOSIS - S. V. Seleznev; I. A. Baranova; E. P. Krivonosova; N. V. Kuvychlina; K. G. Pereverzeva; L. P. Kalinina (Klinicist)
Objective: analysis of clinical features of the dissecting aortic aneurysm (DAA) and factors affecting prognosis in a group of 40 patients, hospitalized in Ryazan Regional Cardiology Dispensary during 2008–2012.Material and methods. We have analyzed clinical data of 40 patients with DAA, assessed their survival and identified factors affecting prognosis.Results. The mean age of the patients was 61.1 ± 15.6 years; 82 % of them were males. 80 % of the patients were hospitalized in the acute period of the disease, 60 % – during the first 24 hours. 4 2 % of the patients had DAA as a referral diagnosis. The main clinical manifestations of DAA included: chest pain and abdominal pain (92 %), weakness (51 %), shortness of breath (28 %), heart disruptions (8 %), dizziness (5 %), and cough (3 %). Pain syndrome was absent in 8 % of the DAA patients. At physical examination 49 % of the patients demonstrated pale skin, 1 patient (3 %) had cyanotic skin. Low blood pressure was observed in 33 % of the cases, tachycardia – in 31 %, and tachypnea – in 13 % of the cases. 26 % of the patients were found to have murmur over the aorta, 10 % – abnormal heart rhythm. 44 % showed tenderness on palpation of the abdomen.Electrocardiography was carried out for 97 % of the study population, chest X-ray for 33 %, transthoracic echocardiography for 4 4 %, and computed tomography (CT) for 42 %, including contrast-enhanced computed tomography scanning for 38 %. 31 % of the patients received antiplatelet agents and anticoagulants. 24 % of the patients underwent surgical treatment in Ryazan» Regional Cardiology Dispensary, 36 % were referred to Federal centers of cardiovascular surgery. In-hospital mortality rate was 52 %, 24-hour mortality rate was 30 %. The following factors were found to be statistically significant in terms of the disease prognosis: systolic and diastolic blood pressure, left ventricular ejection fraction, levels of hemoglobin, blood urea and creatinine.Conclusion. In 8 % of the patients with DAA pain syndrome was not observed. Visualizing examinations (echocardiography, CT), aiding in DAA-diagnosis verification, were performed in less than 50 % of the cases. In-hospital mortality rate among DAA-patients was 52 %, 24-hour mortality rate was 30 %. Lower values of systolic and diastolic blood pressure, left ventricular ejection fraction, lower hemoglobin level together with increased levels of blood urea and creatinine were significantly associated with death.